Auditory Outcomes with Hearing Rehabilitation in Children with Unilateral Hearing Loss: A Systematic Review. (October 2017) - Appachi, Swathi; Specht, Jessica. L.; Raol, Nikhila; Lieu, Judith E. C.; Cohen, Michael S.; Dedhia, Kavita; Anne, Samantha
Objective: Options for management of unilateral hearing loss (UHL) in children include conventional hearing aids, bone-conduction hearing devices, contralateral routing of signal (CROS) aids, and frequency-modulating (FM) systems. The objective of this study was to systematically review the current literature to characterize auditory outcomes of hearing rehabilitation options in UHL. Data Sources: PubMed, EMBASE, Medline, CINAHL, and Cochrane Library were searched from inception to January 2016. Manual searches of bibliographies were also performed. Review Methods: Studies analyzing auditory outcomes of hearing amplification in children with UHL were included. Outcome measures included functional and objective auditory results. Two independent reviewers evaluated each abstract and article. Results: Of the 249 articles identified, 12 met inclusion criteria. Seven articles solely focused on outcomes with bone-conduction hearing devices. Outcomes favored improved pure-tone averages, speech recognition thresholds, and sound localization in implanted patients. Five studies focused on FM systems, conventional hearing aids, or CROS hearing aids. Limited data are available but suggest a trend toward improvement in speech perception with hearing aids. FM systems were shown to have the most benefit for speech recognition in noise. Studies evaluating CROS hearing aids demonstrated variable outcomes. Conclusions: Data evaluating functional and objective auditory measures following hearing amplification in children with UHL are limited. Most studies do suggest improvement in speech perception, speech recognition in noise, and sound localization with a hearing rehabilitation device.